Management of the various factors in Widening of Major Arterial Roads like JVLR in Mumbai - Sheikh, Faraz Gani (International Journal of Computer Sciences and Engineering, 2023)
The effective management of the various factors and hurdles involved in the widening of major arterial roads in big cities, such as JVLR in Mumbai, which is crucial for the success of the project. This involves balancing the need for improved traffic flow with the concerns of local public, daily commuters and finding effective solutions to the challenges posed by land acquisition, traffic management, tackling the underground utilities, co-ordination with the different agencies and BMC’s other department’s requirements. By working closely with local public, commuters, businesses, and BMC’s other departments and implementing effective strategies to minimize the impacts of the project, by keeping rigorous follow up with the agencies involve in risks mentioned above, it is possible to achieve the goals of widening of major arterial road for improved traffic flow and improved quality of life for residents and commuters in Metro Cities, like Mumbai.